Ways to Reduce Inequality in Education between Rural and Urban Populations (on the Example of the Almaty Region) - A. N. Zhanbyrbayeva; A. S. Beimisheva; N. S. Sagidolda; G. A. Andirzhanova (Экономика: стратегия и практика)
This article aims to identify ways to reduce the inequality in education between the rural and urban populations of the Almaty region. The hypothesis is put forward that the solution to the problem of inequality in education in rural areas can be solved by applying a clustering mechanism within the framework of controlled urbanization through the creation of educational development centers based on secondary schools. The research methodology includes the methods of social statistics, methods of analysis of scientific literature, methods of factor analysis, cluster analysis, and mathematical and statistical methods. The section “results and discussions” presents the analysis of the dynamics of educational coverage of graduates of rural and urban schools of the Almaty region, which revealed a catastrophic gap that threatens the region’s sustainable development prospects. The results of a cluster analysis of nine districts of the Almaty region for opportunities for the development of education according to the criteria of the existing material and technical equipment of schools, their level of digitalization, the sufficiency of funding from the local budget, and the development of the accompanying socially significant infrastructure are also presented. According to the analysis, the concept of leveling inequality in education was proposed based on identifying potential locations for creating centers for the development of education in rural areas. In the future, this study can be used for further deployment of regional programs to reduce inequality in education in rural areas.